Numerical investigation on rock‐breaking mechanism and cutting temperature of compound percussive drilling with a single PDC cutter. Issue 12 (16th October 2021) - Wang, Wei; Liu, Gonghui; Li, Jun; Zha, Chunqing; Lian, Wei; Gao, Reyu
Abstract: Compound percussive drilling technology is a new method to improve the rock‐breaking efficiency in deep hard formation. In order to study the rock‐breaking mechanism of compound impact drilling, the thermal‐structure coupling simulation of the dynamic rock‐breaking process with a single PDC cutter was investigated by using ABAQUS software. The influence of impact parameters on the rock‐breaking performance and cutting temperature was analyzed. The results proved that the compound impact load changes the rock failure mode and improves the rock‐breaking efficiency. Compared with steady load cutting, the rock broken volume under compound impact increased by 7.5%, and the mechanical specific energy (MSE) decreased by 12.3%. As the axial impact load amplitude increases, the MSE increases gradually. With an increase in torsional impact load amplitude and impact frequency, the MSE decreases first and then increases, and the optimal torsional static load ratio is 0.3, and the optimal impact frequency is 30 Hz. In addition, the cutting temperature of the compound percussive drilling is higher than that of the steady load cutting, and it increases with the impact load amplitude and decreases with the frequency. For the three impact load waveforms—sine, triangle, and square in this paper, the rock‐breaking efficiency under the condition of sine waveform is the largest when the dynamic amplitude of the pulse force is fixed, and the cutting temperature under the condition of square waveform is the highest. Finally, based on the analysis of the rock‐breaking mechanism, a novel compound percussive drilling tool was designed and tested in the field. Abstract : (1) Compared with steady load cutting, the rock broken volume under compound impact increased by 7.5%, and the mechanical specific energy (MSE) decreased by 12.3%. (2) A novel compound percussive drilling tool was designed based on the analysis of the rock‐breaking mechanism under compound impact load. The axial hammer could generate a square wave, while the torsional hammer could generate a sine wave.